2020
DOI: 10.1051/0004-6361/201937191
|View full text |Cite
|
Sign up to set email alerts
|

Rapid spectral transition of the black hole binary V404 Cygni

Abstract: During the June 2015 outburst of the black hole binary V404 Cyg, rapid changes in the X-ray brightness and spectra were common. The INTEGRAL monitoring campaign detected spectacular Eddington-limited X-ray flares, but also rapid variations at much lower flux levels. On 2015 June 21 at 20 h 50 min, the 3-10 keV JEM-X data as well as simultaneous optical data started to display a gradual brightening from one of these low-flux states. This was followed 15 min later by an order-of-magnitude increase of flux in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…This flare and the outflow was responsible for the rapid rise of N. Additionally, flaring events could also contribute to the rapid variability. On 21 June 21 2015 (MJD 57,194), the B eq was observed to be at an increasing N. On the same day, the rapid variation of the spectral properties was observed [65], although the mass accretion rates did not change.…”
Section: Evolution Of the Spectral Properties With Flaresmentioning
confidence: 92%
“…This flare and the outflow was responsible for the rapid rise of N. Additionally, flaring events could also contribute to the rapid variability. On 21 June 21 2015 (MJD 57,194), the B eq was observed to be at an increasing N. On the same day, the rapid variation of the spectral properties was observed [65], although the mass accretion rates did not change.…”
Section: Evolution Of the Spectral Properties With Flaresmentioning
confidence: 92%
“…The detailed study by Rodriguez et al [415] and Alfonso-Garzón et al [1] showed that on 1-minute and longer time scales, the INTEGRAL OMC, JEM-X and IS-GRI light curves showed: (i) flares where the optical emission was delayed by minutes up to an hour following and strong X-ray flare, (ii) flares where the optical and X-ray emissions were practically simultaneous (i.e. almost the exact same variations were observed ), and 3) flares during which enhanced optical and soft X-ray emissions preceded a hard X-ray flare [209]. Moreover, simultaneous NuSTAR and optical observations taken on sub-second time scales showed that the optical emission lagged the X-rays by roughly 100ms [142,186].…”
Section: Rapid Multi-wavelength Variabilitymentioning
confidence: 99%
“…Longer optical time lags of up to an hour were attributed to interactions between distinct relativistic ejecta in the form of blobs of plasma [1], although on these long time scales the association of a given X-ray flare to its optical counterpart may be in some cases ambiguous given the stochastic nature of the light curves. The few cases where INTEGRAL/OMC/JEM-X/ISGRI detected negative lags, i.e., where the optical (and soft X-ray) emission leads the (hard) X-rays [1,209], remain a puzzle yet to be solved, which could be explained in terms of mass accretion rate fluctuations propagating inwards through the accretion disc.…”
Section: Rapid Multi-wavelength Variabilitymentioning
confidence: 99%